Relationships and processes of families during the COVID-19 lockdown as told by mothers - Pedraza Valdez, Ana Luisa; Maldonado Cervantes, Karla Aimee; García-Solano, Beatriz (Revista Cuidarte, 2023)
Introduction: The state of emergency caused by COVID-19 forced the adoption of social restriction measures to reduce contagion, including lockdowns. They impacted various aspects of human life and considerably affected family dynamics by causing families to remain at home, increasing the coping of crisis, and experiencing a transition to new ways of living. Objective: To analyze the relationships and processes experienced by families during the COVID-19 lockdown as told by mothers. Materials and Methods: A qualitative grounded theory study was conducted using in-depth interviews with five mothers. Results: The results obtained emerged from a core category, “acquisition of new ways of living,” and three categories that support it: 1) Coping with the pandemic onset, 2) adapting to the new normal in the family, 3) embracing the pandemic consequences in everyday life. Discussion: The process that Mexican families have gone through with COVID-19 has been different from that of other countries; living together at home was affected since their freedom to live day to day as they did was compromised. Conclusion: The participants expressed that, during the COVID-19 pandemic, the family underwent a transition process in order to acquire new ways of living, which included habits, customs, and structures that met their needs at that time; this process included different stages (coping, adaptation, and adoption). How to cite this article: Pedraza Valdez Ana Luisa, Maldonado Cervantes Karla Aimee, García Solano Beatriz. Relaciones y procesos de familias en confinamiento por COVID-19 narradas por madres. Revista Cuidarte. 2023;14(1):e2347. http://dx.doi.org/10.15649/cuidarte.2347